Hyperkalemia Associated with Angiotensin Converting Enzyme Inhibitor or Angiotensin Receptor Blockers in Chronic Kidney Disease - Yudi Her Oktaviono; Novia Kusumawardhani (Acta Medica Indonesiana)
Inhibition of the renin-angiotensin-aldosterone system (RAAS) is a key strategy in treating hypertension in cardiovascular and renal diseases. However, RAAS inhibitors (angiotensin-converting enzyme inhibitors, angiotensin receptor blockers, aldosterone receptor antagonists, and direct renin inhibitors) increase the risk of hyperkalemia (serum potassium >5.5 mmol/L). This poses a therapeutic challenge because these patient groups comprise in whom the drugs are therapeutically indicated. Important considerations when initiating ACEI or ARB therapy include obtaining an estimate of glomerular ﬁltration rate and a baseline serum potassium concentration, as well as assessing whether the patient has excessive potassium intake from diet, supplements, or drugs that can also increase serum potassium. Serum potassium monitoring shortly after initiation of therapy can assist in preventing hyperkalemia. If hyperkalemia does develop, prompt recognition of cardiac dysrhythmias and effective treatment to antagonize the cardiac effects of potassium, redistribute potassium into cells, and remove excess potassium from the body is important. Understanding the mechanism of action and monitoring of ACEI and ARB coupled with judicious drug use and clinical vigilance can minimize the risk to the patient of developing hyperkalemia.